PERBEDAAN KINERJA KEUANGAN ANTARA PERBANKAN KONVENSIONAL DAN SYARIAH - Mahrom D.S, Yudha (Jurnal Ilmu Manajemen, 2016)
Formulation of the problem in this research is how the difference in financial performance between conventional and islamic banking, this study was Quantitative and Qualitative. The population in this study is asign the company went public three years, obtained a simple of eight compannies, using simple random sampling technique lottery in determining the sample. The data used are secodary data from company financial statements, hypothesis testing using F and with a significant level of 5%.Aspects that are analyzed in this paper there are five aspects of the use of funds ratio CAR (Current assets Retio), Business efficiency aspect LMR (Lavarage Multiplier Ratio), the aspect of a bank’s ability to pay obligation QR (Quick Ratio), aspect of profitable operations ROI (Return on Investmen) and the capability to meansure business risk DRR (Deposit Risk Ratio).The result showed no difference to the ratio of the CAR to an independent bank and bank BNI QR to test one-on one while the overall ratio only LMR that there are differnces in the financial performance of both conventional and islamic banks. This is due to the amount of funds invested in arriving and it was followed by the still limited bank to repay its obligations to customers.